Tinjauan Fiqih Siyasah Terhadap Implementasi Permendes Nomor 3 Tahun 2015 Berdasarkan Peran Dan Fungsi Pendamping Desa Dalam Menunjang Pembangunan Desa (Studi Kasus di Desa Lae Nuaha Kecamatan Siempat Nempu Hulu Kabupaten Dairi) - Silaban, Budianto (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2024)
ABSTRACTThis research is a field research conducted in Lae Nuaha Village, Siempat Nempu Hulu District, Dairi Regency. The formulation of the problem in this study is how the role of village assistants in village development in implementing Permendes Number 3 of 2015 concerning villages in Lae Nuaha village, Siempat Nempu District, upstream of Dairi Regency, how the function of village assistants in supporting village development based on Law Number 3 of 2015 concerning village assistants from the perspective of fiqh siyasah and how to review fiqh siyasah to Law Number 3 of 2015 related to roles and functions Village assistant in Lae Nuaha Village, Siempat Nempu District, upstream of Dairi Regency. In this study, the author emphasizes the role and function of village assistants in supporting village development as a research sample. In collecting data, the author uses the following methods: Observation , Interview and Documentation. One of the ways to realize village welfare, the regulation of the village minister, the development of disadvantaged areas and transmigration, in this case, forms a village companion to assist the village both in planning, implementation and monitoring of village development. The existence of village assistants is very important in assisting villages to realize village welfare. The compiler aims to find out the roles, functions, and obstacles experienced by village assistants in supporting development in Lae Nuaha village, Siempat Nempu Hulu District, Dairi Regency. Of course, it is very interesting for the author to research, especially in village assistance, the government collaborates with village assistants and village assistants in collaboration with the community in Lae Nuaha Village, Siempat Nempu Hulu District, Dairi Regency. Based on the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Number 3 of 2015 concerning village assistants, the existence of village assistants can be known whether something is running according to the plan or in accordance with the instructions that have been determined. It can be known the advantages and disadvantages of working and it can also be known whether it works effectively or not. However, based on the facts in the field that the existence of the implementation of village assistance has not been maximized in carrying out its role and function as a village assistant, namely the lack of speed of the budget provided by the provincial government to the district government and the district government to the village government, then the lack of facilities so that village assistants are constrained in carrying out their roles and functions, and communication between village assistants and the community so that development is not as fast as possible. in Lae Nuaha Village, Siempat Nempu Hulu District, Dairi Regency Not fulfilled. Keywords: Role, Function, Village Assistant. ABSTRAKPenelitian ini merupakan penelitian Lapangan yang dilakukan di Desa Lae Nuaha Kecamatan Siempat Nempu Hulu Kabupaten Dairi. Rumusan masalah dalam penelitian ini adalah Bagaimana peran pendamping desa terhadap pembangunan desa dalam mengimplementasikan Permendes Nomor 3 Tahun 2015 tentang desa di desa Lae Nuaha Kecamatan Siempat Nempu hulu kabupaten dairi, bagaimana fungsi pendamping desa dalam menunjang pembangunan desa berdasarkan Undang-undang Nomor 3 Tahun 2015 tentang pendamping desa Perspektif fiqih siyasah dan bagaimana tinjauan fiqih siyasah terhadap Undang-undang Nomor 3 Tahun 2015 terkait peran dan fungsi pendamping desa di desa lae nuaha kecamatan siempat nempu hulu kabupaten dairi. Dalam penelitian ini penulis mentepkan peran dan fungsi pendamping desa dalam menunjang pembangunan desa sebagai sample penelitian. Dalam mengumpulkan data penulis menggunakan cara: Observasi (Pengamatan), Interview (Wawancara) dan Dokumentasi. Salah satu dalam mewujudkan kesejahteraan desa, peraturan menteri desa, pembangunan daerah tertinggal dan transmigrasi dalam hal ini membentuk pendamping desa untuk mendampingi desa baik dalam perencanaan, pelaksanaan dan pemantauan terhadap pembangunan desa. Keberadaan pendamping desa sangatlah penting dalam mendampingi desa untuk mewujudkan kesejahteraan desa. Penyusun bertujuan untuk mengetahui Peran, Fungsi, dan kendala-kendala yg dialami pendamping desa dalam menunjang pembangunan yang ada di desa Lae Nuaha Kec. Siempat Nempu Hulu Kab. Dairi. Tentunya sangat menarik bagi penulis untuk meneliti khususnya dalam pendampingan desa, pemerintah bekerja sama dengan pendamping desa serta pendamping desa bekerja sama dengan Masyarakat yang ada di Desa Lae Nuaha Kec. Siempat Nempu Hulu Kab. Dairi. Berdasarkan Peraturan Menteri Desa, Pembangunan Daerah Tertinggal dan Transmigrasi Nomor 3 Tahun 2015 tentang pendamping desa, adanya pendamping desa dapat diketahui apakah sesuatu berjalan dengan rencana atau sesuai dengan intruksi yang di telah ditentukan. Dapat diketahui kelebihan dan kelemahan dalam bekerja serta dapat diketahui juga apakah bekerja secara efektif atau tidak. Namun berdasarkan fakta yang ada dilapangan bahwa keberadaan pelaksanaan pendampingan desa belum maksimal dalam melaksanakan peran dan fungsinya sebagai pendamping desa, yaitu kurang cepatnya anggaran yg di berikan pemerintah provinsi kepada pemerintah kabupaten serta pemerintah kabupaten kepada pemerintah desa, kemudian kurangnya Fasilitas sehingga pendamping desa terkendala dalam melaksanakan peran dan fungsinya, dan komunikasi antara pendamping desa dengan masyarakat sehingga pembangunan yg ada di Desa Lae Nuaha Kec. Siempat Nempu Hulu Kab. Dairi Tidak terpenuhi.Kata Kunci: Peran, Fungsi, Pendamping Desa.